Newborn with Prenatally Diagnosed Choroidal Fissure Cyst and Panhypopituitarism and Review of the Literature - Chitkara, Ritu; Rajani, Anand; Bernstein, Jonathan; Shah, Sejal; Hahn, Jin S; Barnes, Patrick; Hintz, Susan R (American Journal of Perinatology Reports, 2011)
Little has been reported on fetal diagnosis of choroidal fissure cysts and prediction of the clinical complications that can result. We describe the case of a near-term male infant with prenatally diagnosed choroidal fissure cyst and bilateral clubfeet. His prolonged course in the neonatal intensive care nursery was marked by severe panhypopituitarism, late-onset diabetes insipidus, placement of a cystoperitoneal shunt, and episodes of sepsis. Postnatal genetic evaluation also revealed an interstitial deletion involving most of band 10q26.12 and the proximal half of band 10q26.13. The patient had multiple readmissions for medical and surgical indications and died at 6 months of age. This case represents the severe end of the spectrum of medical complications for children with choroidal fissure cysts. It highlights not only the importance of comprehensive evaluation and multidisciplinary management and counseling in such cases, but also the need for heightened vigilance in these patients.
Keywords: Choroidal fissure cyst; panhypopituitarism; neonate